Pengaruh Profitabilitas, Likuiditas, Solvabilitas, dan Aktivitas Terhadap Financial Distress (Studi Pada Perusahaan Food and Beverage yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2023) - Adinda Paulina Puspitasari; Iman Karyadi (JURNAL RISET AKUNTANSI TIRTAYASA, 2025)
The objectives of this research are: 1) To determine the effect of Profitability on Financial distress in food and beverage companies listed on the Indonesia Stock Exchange for the 2021-2023 period. 2) To determine the effect of Liquidity on food and beverage companies listed on the Indonesia Stock Exchange 2021-2023 period. 3) To determine the effect of Solvency on food and beverage companies listed on the Indonesia Stock Exchange 2021-2023 period. 4) To determine the effect of Activity on Financial distress in food and beverage companies listed on the Indonesia Stock Exchange for the 2021-2023 Period. The independent variables in this study are Profitability, Liquidity, Solvency, and Activity. while the dependent variable in this study is Financial distress. Sample determination using explanatory quantitative methods. The sampling technique uses purposive sampling. The population used in this study is food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023 and the number of samples is 13 companies. The analysis technique for Hypothesis Testing uses Multiple Linear Regression. The results showed that Profitability has a effect on Financial distress, Liquidity has a effect on Financial distress, Solvency do not effect on Financial distress, Activity has a positive effect on Financial distress. Keywords: Profitability, Liquidity, Solvency, and Financial distress Activity